Pengaruh Faktor Makroekonomi Nasional Terhadap Indeks Harga Saham Gabungan Di Bursa Efek Indonesia: Studi Kasus 2018-2022 - Mutiara, Kharisma; Jojok Dwiridotjahjono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Although an increase in investments can have an impact on a nation's economic growth, it is impossible to forecast a nation's future economic circumstances or obstacles. This research examines how the Indonesia Stock currency Composite Index (IHSG) is affected by foreign currency rates, inflation, and the BI Rate (Bank Indonesia Rate) between 2018 and 2022. Saturated sampling is used to select a sample size of 60 data points for each variable from the 60 monthly closing price data of IHSG collected over the last five years, using secondary data from official online business and financial portals. To assess how these macroeconomic factors affect the IHSG, the study uses1multiple linear1regression1analysis. The1findings show1that the IHSG is impacted by all three variables at the same time. However, the foreign exchange rate has no discernible effect1on the IHSG, but inflation and the BI Rate alone have a large impact. The1relationship between1macroeconomic variables1and Indonesia's stock1market performance is better understood thanks to these findings.